MENINGKATKAN KEMAMPUAN TEKNIK PENJUALAN PADA UKM - Djakasaputra, Arifin; Puspita, Elizabeth Christinio (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2023)
In a competitive business era, sales skills are crucial for every salesperson to face market competition. This article discusses the importance of an in-depth understanding of the goods or services sold by the company as well as expertise in applying effective sales techniques. The main focus is on the role of the salesperson in optimizing the sales of services and goods. This research was conducted with the aim of helping business owners, particularly in the culinary industry in Jambi, to improve their understanding and skills in sales techniques. The method used involved training and socialization to business partners, covering in-depth introduction to product offering techniques, handling buyer rejection, and coping strategies.The results of the research activities showed that the training provided significantly improved the partners' sales technique skills. Business partners were able to optimize their skills in selling products to end consumers. In addition, the partners' active participation in the training process was reflected in the two-way discussion between the research team and business partners. The enthusiasm shown by the partners in receiving the training materials confirmed the success of the activities in having a positive impact on the partners' sales skills. This research provides an important contribution for business owners, especially in the culinary sector, in improving the efficiency and effectiveness of sales techniques